Investment Responses to Tax Policy Under Uncertainty - Irem Guceri; Maciej Albinowski (Center for Economic Studies and ifo Institute (CESifo), 2019)
How does economic uncertainty affect the impact of tax policy? We exploit a natural experiment in which two very similar investment subsidies were implemented in the same country, two years apart: once during a period of economic stability, and once during a period of very high uncertainty. Exploiting sharp discontinuities in eligibility and using rich administrative data, we find that firms exposed to high uncertainty decide to "wait and see" before investing, despite generous incentives. Firms that are sheltered from uncertainty still respond strongly to policy. This implies that periods of stability offer an important policy opportunity to encourage investment.
Keywords: H25; D25; C21; 330; investment; uncertainty; tax policy